Social representations of nursing students about obstetric violence: study with a structural approach - Amanda de Alencar Pereira Gomes; Renara Meira Gomes; Margaret Olinda de Souza Carvalho e Lira; Cleuma Sueli Santos Suto; Juliana Costa Machado; Vanda Palmarella Rodrigues (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To learn about the structure of nursing students' social representations about obstetric violence. Method: Qualitative study conducted with 117 nursing students from a state university in Brazil, between July and October 2022. Data were collected in person using the free Word evocation technique and processed using the Evoc software to create a four-box chart, through prototypical analysis. Results: The representational structure was organized on the central elements of disrespect, suffering and violation, which attribute to the representation negative meanings related to the group's position on the grievance and its repercussions. The similarity analysis showed that the elements with the greatest connection were disrespect and suffering. Final considerations: Social representations of nursing students were organized around an attitudinal dimension through the terms disrespect and violation, and the affective dimension defined by suffering. It is noteworthy that, for students, obstetric violence is centered on disrespectful professional practices that cause suffering to women.